Structure and properties of composite reinforcement with unidirectional fibers - Tepla, Tetiana; Kovbasiuk, Taras; Lemishka, Ihor; Palchevskii, Maksym (Видавництво Львівської політехніки, 2024)
This work considers the actual problem of using composite reinforcement in building structures. Traditional steel fittings have some disadvantages, such as susceptibility to corrosion, heavy weight, and the need for frequent maintenance. Composite materials, unlike metals, are lighter, stronger, and less prone to corrosion, which increases the durability of structures and reduces operating costs. In the work, a structural analysis of the composite armature was carried out using modern microscopic methods, making it possible to identify certain structural defects. The ImageJ software package used in the study made it possible to conduct a detailed quantitative analysis of the structure of the composite armature. Thanks to the capabilities of automatic processing of microstructural images, ImageJ provided an accurate determination of the area of fibers, their diameters, and distribution in the material. This greatly simplified analyzing the composite structure and allowed for a more objective assessment of reinforcing quality. The use of ImageJ made it possible to increase the accuracy of research and provided an opportunity to quickly process large volumes of data. In addition, the microhardness study showed a significant difference in hardness between the matrix and the reinforcing fibers, highlighting the anisotropy of the material properties. The authors recommend improving the mechanical properties of composite reinforcement due to the distribution of fibers in several directions. The use of composite materials is promising, especially in aggressive environments and with increased energy efficiency requirements.
Keywords: composite; reinforcement; mictostructure; fibers; microhardness